A DNA Damage Repair Gene Signature Associated With Immunotherapy Response and Clinical Prognosis in Clear Cell Renal Cell Carcinoma - Peng, Linjie; Liang, Jiaming; Wang, Qi; Chen, Guodong (Frontiers in Genetics, 2022)
Background: Clear cell renal cell carcinoma (ccRCC) is the most common subtype in renal cell carcinoma with relative poor clinical outcomes. DNA damage repair genes (DDRGs) as potential biomarkers are rarely reported in predicting immunotherapy response and clinical prognosis for ccRCC. Methods: RNA-seq and clinical data of ccRCC cohort were collected form TCGA database. Univariate Cox regression and LASSO analysis were performed to construct a DDRGs risk signature. Functional enrichment analysis was performed to explore latently enriched pathways associated with DDRGs signature. Immune cell infiltration level was estimated using gene set enrichment analysis, and immune response of ccRCC was predicted by tumor immune dysfunction and exclusion(TIDE) algorithm. To predict 1-, 3- and 5-year overall survival(OS), a nomogram was constructed based on independent prognostic factors, whose performance would be evaluated by calibration curve. Results: A total of 47 DNA damage repair related genes (DDRGs) with significant prognostic value were identified in the ccRCC cohort(n= 519). A DDRGs risk signature comprising six DRRGs (MSH3, RAD54L, RAD50, EME1, UNG and NEIL3) were constructed by LASSO analysis. ccRCC patients were then divided into low- and high-risk group based on the risk score. Survival analysis revealed that patients in high-risk groups exhibited significantly poorer OS and progression-free survival (PFS), as was confirmed by the testing dataset. Functional enrichment analysis indicated that differentially expressed genes (DEGs) between high- and low-risk groups were mainly associated with immune-related biological processes in ccRCC, among which immunodeficiency pathway was significantly enriched in high-risk group. Though the risk signature was significantly correlated with the immune cell infiltration, but PD-1 and PD-L1 were less expressed in the DDRGs signature, which might indicate the poor response to immunotherapy in high-risk group. Furthermore, the Cox regression analysis indicated that the DDRGs signature can be served as an independent prognostic predictor when compared to clinical characteristics. Based on the independent prognostic predictors, we constructed a nomogram with excellent predictive ability in OS prediction for ccRCC patients. Conclusion: We developed a reliable DDRGs risk signature that can independently predict the OS and PFS of ccRCC, which is also promising for predicting immunotherapeutic response in ccRCC patients.